Formulation and evaluation of herbal shower gel using various malaysian plant and herbal extracts - Mas Aimma, Abu Bakar; Wan Nurul Huda, Wan Zainal; Mohd Aizudin, Abd Aziz; Mohd Azmir, Arifin
This study addresses concerns over synthetic additives in commercial personal care products, such as triclosan, known for adverse effects on skin and endocrine health. Focusing on herbal shower gels, natural alternatives from local Malaysian plants and herbs—Azadirachta indica, Aloe barbadensis miller, Propolis, Ginger, Papaya, Pomegranate, Piper betle, Centella asiatica, and Camellia sinensis—were formulated to provide effective cleansing while minimizing adverse reactions. Physicochemical parameters including organoleptic evaluation, pH, foaming ability and stability, viscosity, solubility, antibacterial activity, and sensory analysis were assessed. The formulations exhibited promising antibacterial efficacy against Staphylococcus aureus and Escherichia coli, with no observed skin irritation among consumers during sensory analysis. These findings underscore the importance of exploring natural alternatives in personal care product formulations to address health and environmental concerns associated with synthetic additives.